2023
DOI: 10.1038/s41598-023-33277-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel Alzheimer’s disease prognostic signature: identification and analysis of glutamine metabolism genes in immunogenicity and immunotherapy efficacy

Abstract: Alzheimer’s disease (AD) is characterized as a distinct onset and progression of cognitive and functional decline associated with age, as well as a specific neuropathology. It has been discovered that glutamine (Gln) metabolism plays a crucial role in cancer. However, a full investigation of its role in Alzheimer’s disease is still missing. This study intended to find and confirm potential Gln-related genes associated with AD using bioinformatics analysis. The discovery of GlnMgs was made possible by the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The methodologies proposed by Zi-Xuan Wu et al in 2023 were employed in this study [ 18 ]. NSOI patients' data were gathered from GEO databases, and the GlnMgs were then matched to perform difference analysis and risk model creation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The methodologies proposed by Zi-Xuan Wu et al in 2023 were employed in this study [ 18 ]. NSOI patients' data were gathered from GEO databases, and the GlnMgs were then matched to perform difference analysis and risk model creation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have emphasized the role of GlnMRGs in various non-tumor age-related diseases. For example, Wu et al established metabolic characteristic models for Alzheimer's disease [ 12 ] and osteoporosis [ 34 ] related to glutamine metabolism. The physiological role of glutamine metabolism in the progression of DFU is not yet clear, and this could be an interesting research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that manipulating glutamine metabolism presents a promising strategy to transition tumor-associated macrophages from an M2 phenotype to an M1 phenotype, thereby bolstering anti-tumor inflammatory immune responses. Moreover, the metabolism of glutamine also exerts an impact on Th1 cell differentiation and the activation of effector T cells, underscoring its potential to reshape the tumor microenvironment and enhance the efficacy of immunotherapy [ 12 ]. Although the combination of targeting glutamine along with immunotherapy shows significant promise in oncology, our comprehension of the precise role of glutamine metabolism in immunogenicity and immunotherapy remains constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine (Gln) metabolism plays a crucial role in tumors. Wu et al (2023) reported the identification of four potential Gln-related genes associated with AD through WGCNA. The analysis of their biological functions emphasized their role in determining cell fate, atrioventricular canal development, and neuronal fate.…”
Section: Identification Of Candidate Biomarkers Associated With the B...mentioning
confidence: 99%